2017
DOI: 10.1186/s11671-017-1935-x
|View full text |Cite
|
Sign up to set email alerts
|

Nanooxide/Polymer Composites with Silica@PDMS and Ceria–Zirconia–Silica@PDMS: Textural, Morphological, and Hydrophilic/Hydrophobic Features

Abstract: SiO2@PDMS and CeO2–ZrO2–SiO2@PDMS nanocomposites were prepared and studied using nitrogen adsorption–desorption, Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), measurements of advancing and receding contact angles with water, and microcalorimetry. The pore size distributions indicate that the textural characteristics change after oxide modification by poly(dimethylsiloxane) (PDMS). Composites are characterized by mainly mesoporosity and macroporosity of aggregates of oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…For the DMDCS-treated sample, the FTIR spectra intensity of the O-H vibrations at 3364 cm -1 decreased gradually with increasing polymer absorption. This suggests that a notable amount of surface hydroxyls was disturbed by the DMDCS chains and that the amount of adsorbed water decreases (Sulym et al 2017). The band at 2960 cm -1 , i.e., the symmetric and asymmetric C-H stretching vibrations of the methyl groups, was also slightly enhanced.…”
Section: Surface Hydrophobicitymentioning
confidence: 96%
See 2 more Smart Citations
“…For the DMDCS-treated sample, the FTIR spectra intensity of the O-H vibrations at 3364 cm -1 decreased gradually with increasing polymer absorption. This suggests that a notable amount of surface hydroxyls was disturbed by the DMDCS chains and that the amount of adsorbed water decreases (Sulym et al 2017). The band at 2960 cm -1 , i.e., the symmetric and asymmetric C-H stretching vibrations of the methyl groups, was also slightly enhanced.…”
Section: Surface Hydrophobicitymentioning
confidence: 96%
“…The WCA is an evaluation index for the hydrophobic performance of a surface (Olin et al 2013;Sulym et al 2017). A membrane surface with a WCA value greater than 90° is hydrophobic, and a surface with a value greater than 150° is generally considered to be superhydrophobic (Huang et al 2016).…”
Section: Sample Preparation For Wca Testmentioning
confidence: 99%
See 1 more Smart Citation
“…CeO 2 proved to be an efficient reinforcing agent for natural rubber [17]. As additives to silicones, generally, in studies reported in literature [9,18], REO have been used together with silica (Ceria/Silica [9] or Ceria-Zirconia-Silica@PDMS [18]). There is a report in 1974 [19] about the thermostabilizing effect of rare-earth metal oxides on methylvinylsilicone rubbers.…”
Section: Introductionmentioning
confidence: 99%
“…Note that different aspects of the interactions of PDMS-hydrophobized silicas with water, as well as other adsorbates, have been analyzed elsewhere. 41,50,6265 Typically, uniform hydrophobic surfaces, for example, modified by PDMS fragments, are characterized by a contact angle for settled water drops not greater than θ c = 120°. Nano/microstructured hydrophobic particles (structures) can provide much larger θ c —up to 170° due to a surface geometry factor.…”
Section: Introductionmentioning
confidence: 99%